Santri Ex-Social Pathology Perpetrators at Ora Aji Islamic Boarding School Sleman Yogyakarta: Transformation of Religiosity through Religious Conversion - Syahnaidi, Muhammad Amin Qodri; Junaid, M. (Proceeding International Conference on Religion, Science and Education, 2022)
This research aims to know the reasons and transformation of religiosity through the religious conversion by santri ex-social pathology perpetrators at Ora Aji Islamic Boarding School Sleman Yogyakarta. This research is qualitative with the phenomenology and psychology of religion approaches. The data were collected through observation, interviews, and documentation. Data were analyzed with reduction, data presentation, and concluding. The research of this paper can be concluded into three keys: first, 4 factors affecting the five subjects to do the transformation of religiosity in the form of religious conversion, namely divine, liberation from mental stress, educational and socialization situations, and various social influences. Second, the process of transformation of religiosity in the form of religious conversion experienced by the five subjects covers five stages including calm period, non-calm period, conversion period, calm period, and expression of the conversion period. Third, santri ex-social pathology perpetrators reframe religious attributes by negotiating tattoos with pesantren symbols such as cap (peci) and sarong resulting in a new term of santri tatoan. Santri ex-social pathology perpetrators in Ora Aji Islamic Boarding School run their daily life by learning Islamic education and yaumiyah activities. Santri ex-social pathology perpetrators also start expressing their attitude and behavior as santri in daily life in Ora Aji Islamic Boarding School.